2005
DOI: 10.1111/j.1525-1470.2005.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Sun Protection Policies in Miami‐Dade County Public Schools: Opportunities for Skin Cancer Prevention

Abstract: Childhood exposure to ultraviolet radiation from the sun and a history of sunburns are risk factors for skin cancer. Because children spend time outdoors when they are at school, school sun protection policies are an important health issue, particularly in areas of the country with year-round warm and sunny climates, such as Florida. To better understand the sun protection policies and practices in South Florida schools, a sample (n = 51) of elementary and middle schools in Miami-Dade County public schools wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…Different studies have shown significant associations between sun exposure and the occurrence of this kind of cancer, especially among those who work outdoors. 11,15,16 Physical education teachers belong to the group of workers who carry out their tasks exposed to the sun and, therefore, are vulnerable to skin cancer 16.17 These professionals, according to research conducted in the United States, may be exposed to the sun for 4.5 hours per day 17 , and according to a study conducted in Australia, they have been exposed to high levels of solar radiation. 10 In athletes, frequent exposure to the sun has also been a concern.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown significant associations between sun exposure and the occurrence of this kind of cancer, especially among those who work outdoors. 11,15,16 Physical education teachers belong to the group of workers who carry out their tasks exposed to the sun and, therefore, are vulnerable to skin cancer 16.17 These professionals, according to research conducted in the United States, may be exposed to the sun for 4.5 hours per day 17 , and according to a study conducted in Australia, they have been exposed to high levels of solar radiation. 10 In athletes, frequent exposure to the sun has also been a concern.…”
Section: Discussionmentioning
confidence: 99%
“…Although 1 of the 2 recommendations was to parents, only 21% of the schools shared these guidelines with parents. 10 Interviews with key school officials were revealing: many were open to new school sun protection policies but were hamstrung with problems such as negligible funding for school improvements, relatively low priority for sun protection, and the view that sun protection is the parents' responsibility. Pilot, state, and federally funded demonstration projects that provide financial support and infrastructure for school districts to experiment with different methods of crafting new policies should be advocated.…”
Section: Commentmentioning
confidence: 99%
“…It has been noted that after the implementation of education programs sun protection measures are more widely adopted, something that did not happen in our study, mainly because the intervention was an isolated one-off effort that was not continued in order to increase knowledge and have an impact on the students' attitudes (Hewitt et al, 2001;Kirsner et al, 2005;Milne et al, 2006;Roberts et al, 2009;.…”
Section: Assessment Of Knowledge and Attitudes Before And After The Imentioning
confidence: 87%
“…International studies confirm our findings, although place of residence has not been studied well enough yet as a factor that could effect sun protection attitudes. It should be noted that sun protection should not be important only in coastal areas, but rural areas as well, since children there tend to stay outdoors for long duration (Hewitt et al, 2001;Kirsner et al, 2005;Wright et al, 2008).…”
Section: Assessment Of Knowledge and Attitudes Before And After The Imentioning
confidence: 99%
See 1 more Smart Citation